A stationary equilibrium model of green technology adoption with endogenous carbon price - Dammann, Felix,Ferrari, Giorgio (Center for Mathematical Economics (IMW), Bielefeld University, 2024)
This paper proposes and analyzes a stationary equilibrium model for a competitive industry which endogenously determines the carbon price necessary to achieve a given emission target. In the model, firms are identified by their level of technology and make production, entry, and abatement decisions. Polluting firms are subject to a carbon price and abatement is formulated as an irreversible investment, which entails a sunk cost and results in the firms switching to a carbon neutral technology. In equilibrium, we identify a carbon price and a stationary distribution of incumbent, polluting firms, that guarantee the compliance with a certain emission target. Our general theoretical framework is complemented with a case study with Brownian technology shocks, in which we discuss some implications of our model. We observe that a carbon pricing system alongside installation subsidies and tax benefits for green firms trigger earlier investment, while higher income taxes for polluting firms may be distorting. Moreover, we discuss the role of a welfare maximizing regulator, who, by optimally setting the emission target, may mitigate or revert some parameters' effects observed in the model with fixed limit.
urn:nbn:de:0070-pub-29874160
Keywords: Graue Literatur; Emissionshandel; Treibhausgas-Emissionen; Ökosteuer; Umwelttechnik; Innovationsakzeptanz; Stationarität; Gleichgewichtsmodell